Impact of the COVID-19 pandemic on oral health and psychosocial factors - Ciardo, Antonio; Simon, Marlinde M.; Sonnenschein, Sarah K.; Büsch, Christopher; Kim, Ti-Sun (Scientific reports, 2022)
The objective of this study was to investigate oral health-related quality of life (OHRQoL) in times of the COVID-19 pandemic and to examine a possible association to psychosocial factors like psychological stress and symptoms of depression and anxiety disorders. Secondary research questions were whether people changed oral hygiene regimens during the COVID-19 pandemic and to what extent dental symptoms existed and developed compared to pre-pandemic. For this cross-sectional study a survey has been conceptualized to determine OHRQoL, stress, depression and anxiety and their specific confounders in a German cohort. Validated questionnaires as OHIP-G14, PHQ-Stress and PHQ-4 have been implemented. Altogether 1178 participants completed the survey between May and August 2020. The overall OHIP-G14 sum score of 4.8 +/- 7.5 indicated good OHRQoL. 21% of the participants (n = 248) reported toothache, 23% (n = 270) mucosal problems, 31% (n = 356) hypersensitivity of the teeth and 27% (n = 305) myofacial pain. The PHQ-Stress score (4.5 +/- 3.5) demonstrated a mild severity of stress. Depression and anxiety level has been mild to moderate (PHQ-4 score: 2.4 +/- 2.6). 38% of the participants stated subjectively greater emotional burden compared to pre-pandemic. Statistically significant differences exist for OHRQoL, stress, anxiety and depression levels between participants with greater, equal or less emotional burden compared to pre-pandemic. COVID-19 history and aggravated levels of depression, anxiety, and stress seem to associate with lower OHRQoL. Psychosocial consequences during pandemic times and their association to oral health should be further investigated.